Kewajiban Pemberian Jasa Hukum Secara Cuma-Cuma Oleh Notaris Pada Orang Tidak Mampu - Sridana, Claudia Verena Maudy; Westra, I Ketut (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020)DO - 10.24843/AC.2020.v05.i03.p02, 2020)
As a public official who works as a notary public has the authority to be able to make an authentic deed. As a notary in carrying out his commitment to make an authentic deed, the Notary gets approval to provide his services for free or voluntarily to people who are not capable in the financial field. How can you ask for legal assistance by a notary in the free notary area for people who can't afford it? Problems related to legal notifications to notaries who refuse to provide legal assistance in the field of notary to those who are unable? The purpose of the discussion is to analyze and discuss the request for legal assistance by a notary in the notary sector not providing legal assistance in the notary sector for people who cannot afford. This research uses empirical legal research methods, primary data and secondary data obtained were analyzed qualitatively and arranged systematically, which was collected by literature study and interview techniques. The conclusion of this research is the notary in providing his services without collecting honorariums is not only given to people who can not afford it, but notaries can provide free services to those who want to make a foundation or activities in the social, social and dialogue. The legal consequences of notaries who are reluctant to provide legal assistance to people who are not in accordance with the provisions of the sanctions provided for in Article 37 paragraph (2) of the UUJN are also in accordance with the provisions in the Code of Ethics I.N.I.